MANAJEMEN PENGGUNAAN OBAT ANTIDIABETES ORAL PADA PASIEN DIABETES MELLITUS DI PUSKESMAS KABUPATEN GROBOGAN - W.S., F.X. Sulistiyanto; Anggoro, Aloysius Barry; Nur Ain’ni, Charisma Ayu (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Diabetes mellitus is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels exceeding normal limits >140 mg/dL. Prevalence data from the International Diabetes Federation (IDF) predicts that there will be 536.6 million adults aged 20-79 years in the world who suffer from diabetes in 2021, or the equivalent of a prevalence rate of 10.5% of the total population at the same age. The success of a disease therapy is not only influenced by the accuracy of the diagnosis, the selection and administration of the right drug, but compliance in the use of drugs is a determinant of success in the therapy of a disease. The purpose of this study was to determine the characteristics and level of adherence to the use of oral antidiabetic drugs in patients with type 2 DM at Grobogan District Health Center. The type of research used is observational research using descriptive methods. Sampling used a purposive sampling technique with a total sample of 100 patients. The data collection instrument used the MMAS-8 questionnaire to see the level of adherence in diabetes mellitus patients. The results of this study indicate that the level of adherence to drug use in type 2 DM patients at Public Health Center was obtained in the "High Compliance" category of 21 patients (53%) in prolanis respondents and the "Medium Compliance" category was obtained in 24 patients (40%) in respondents non prolanis.